Cascade radical cyclization/cross-coupling of halobenzamides by synergistic Cu/Fe catalysis: An access to 7-tert-alkylated isoquinolinediones. Issue 45 (8th November 2018) - Li, Zeng-Zeng; Yu, Jian; Wang, Liang-Neng; Chen, Shi-Lu; Sheng, Rui-Long; Tang, Shi
Abstract: A Cu/Fe-cocatalyzed cyclization of halobenzamides with azo reagents involving regioselective radical/radical cross-coupling toward functionalized isoquinolinediones was developed. Applying azo reagents as the coupling partner, in the presence of cheap, facile and ligand-free catalytic combination of CuI/Fe(NH4 )2 (SO4 )2 ·6H2 O/air, the halobenzamide radicals generated by a prior radical addition/cyclization process underwent radical/radical cross-coupling via the cleavage of C-X (X = F, Cl, Br, I, OMe, OBn) bond with excellent site selectivity, leading to a series of isoquinolinediones furnished dual distal α-functional quaternary moieties. In addition, the theoretical calculation on the C-X bond cleavage and the positional selectivity using unrestricted density functional theory (DFT) was also conducted. Graphical abstract: